Selection Forces Driving Herding of Herbivorous Insect Larvae - Despland, Emma (Frontiers in Ecology and Evolution, 2021)
Herding behavior is widespread among herbivorous insect larvae across several orders. Most herds arise from an egg-mass and so are sib-groups, but they often fuse into multifamily groups and the few species that have been tested show no evidence of kin-recognition. Species vary in complexity of social behavior but what they have in common includes exhibiting specialized social behaviours that are ineffective in isolated individuals. These behaviours, when performed in groups, are advantageous both to the individual performing them and to colony-mates. They hence constitute cooperation with direct advantages that doesn’t require kinship between cooperators to be adaptive. Examples include: trail following, head-to-tail processions and other behaviours that keep groups together, huddling tightly to bask, synchronized biting and edge-feeding to overwhelm plant defenses, silk production for shelter building or covering plant trichomes and collective defensive behaviours like head-swaying. Various selective advantages to group living have been suggested and I propose that different benefits are in play in different taxa where herding has evolved independently. Proposed benefits include those relative to selection pressure from abiotic factors (e.g. thermoregulation), to bottom-up pressures from plants or to top-down pressures from natural enemies. The adaptive value of herding cooperation must be understood in the context of the organism’s niche and suite of traits. I propose several such suites in herbivorous larvae that occupy different niches. First, some herds aggregate to thermoregulate collectively, particularly in early spring feeders of the temperate zone. Second, other species aggregate to overwhelm host plant defenses, frequently observed in tropical species. Third, species that feed on toxic plants can aggregate to enhance the warning signal produced by aposematic coloration or stereotyped behaviors. Finally, the combination of traits including gregariousness, conspicuous behavior and warning signals can be favored by a synergy between bottom-up and top-down selective forces: when larvae on toxic plants aggregate to overcome plant defenses, this grouping makes them conspicuous to predators and favors warning signals. I thus conclude that a single explanation is not sufficient for the broad range of herding behaviours that occurs in phylogenetically diverse insect larvae in different environments.